2021
DOI: 10.2174/1566524020666201203164910
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the PI3K/AKT/mTOR Signalling Pathway in Male Reproduction

Abstract: : Male fertility is closely related to the normal function of the hypothalamic-pituitary-testicular axis. The testis is an important male reproductive organ that secretes androgen and produces sperm through spermatogenesis. Spermatogenesis refers to the process by which spermatogonial stem cells (SSCs) produce highly differentiated spermatozoa and is divided into three stages: mitosis, meiosis and spermiogenesis. Spermatogenesis requires SSCs to strike a proper balance between self-renewal and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Notably, the PI3K-Akt signaling pathway was found to be the most significant enrichment pathway for all DEGs. Many studies have demonstrated that the PI3K-Akt signaling pathway was involved in the regulation of spermatogenesis ( Duan et al, 2016 ; Deng et al, 2020 ; Ni et al, 2020 ). In brief, our findings suggested that the DEGs were strongly associated with the testis development and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the PI3K-Akt signaling pathway was found to be the most significant enrichment pathway for all DEGs. Many studies have demonstrated that the PI3K-Akt signaling pathway was involved in the regulation of spermatogenesis ( Duan et al, 2016 ; Deng et al, 2020 ; Ni et al, 2020 ). In brief, our findings suggested that the DEGs were strongly associated with the testis development and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the impairment of spermatogenesis may be caused by abnormal lipid and energy metabolism in testis via the downregulation of PPARs mediated by Triptolide ( Ma et al, 2015 ). The involvement of the PI3K-Akt signaling pathway has been confirmed in multiple associations of male reproduction, including the regulation of the hypothalamic-pituitary-gonadal axis, the proliferation and differentiation of spermatocytes, and the regulation of sperm autophagy and testicular endocrine function during sperm development ( Deng et al, 2021 ). Typically, the regulatory subunit gets activated after PI3K activation.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the PI3K-Akt, MAPK and apoptosis pathways, in which YSTLF-associated hub targets were enriched, are closely related to oligoasthenozoospermia. The PI3K/Akt signaling pathway can participate in many important processes of male reproduction, such as the proliferation, differentiation, growth and apoptosis of spermatogonia and regulation of the hypothalamic-pituitary-gonad (HPG) axis during spermatogenesis [ 52 ]. Hypoxia and oxidative stress can inhibit the PI3K/Akt signaling pathway, reducing the level of Akt phosphorylation and inducing cell apoptosis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and oxidative stress can inhibit the PI3K/Akt signaling pathway, reducing the level of Akt phosphorylation and inducing cell apoptosis [ 53 ]. Other studies have demonstrated that activation of the PI3K/Akt pathway may protect testicular cells from apoptosis in the offspring of mice after direct maternal exposure to di-(2-ethylhexyl) phthalate (DEHP) [ 52 , 54 ]. In another study, suppression of the PI3K/Akt pathway associated with oxidative stress may lead to aflatoxin B 1 (AFB 1 )-induced testicular damage and promote autophagy [ 55 ].…”
Section: Discussionmentioning
confidence: 99%